Attention and Skepticism: Influence on Ad Evaluation with Greenwashing - Andreoli, Tais Pasquotto (2024)
The purpose of this study was to analyze the influence of attention and skepticism in the evaluation of false market discourse with an environmental appeal (greenwashing). The theoretical support for the research was based on the study of the attention process (understood in terms of pre-attention and attention), as well as the practice of greenwashing and consumer skepticism. The methodological procedure adopted a hypothetical-deductive approach, carried out through two face-to-face experiments (n=129 and n=159) with a 2 factorial design (attention/pre-attention) x 2 (present/absent skepticism), with the measurement of four interest metrics (attribute evaluation, judgment about the practice of greenwashing, emotional reaction to the advertisement, and environmental purchase behavior), added to eye tracking. One-way ANOVA was used for one-dimensional analyzes and general linear model (GLM) ANOVA for multivariate analyses, with Tukey’s post hoc test. As a result, it was possible to observe a better evaluation of the practice of greenwashing when pre-attentiveness and the absence of skepticism were combined, which sets up a potential scenario for the influence of this false marketing discourse on consumer behavior.